Synthesis, characterization and assessment of hydrophilic oxidized carbon nanodiscs in bio-related applications. Issue 1 (19th December 2017) - Zygouri, Panagiota; Tsoufis, Theodoros; Kouloumpis, Antonios; Patila, Michaela; Potsi, Georgia; Sevastos, Apostolos A.; Sideratou, Zili; Katsaros, Fotios; Charalambopoulou, Georgia; Stamatis, Haralambos; Rudolf, Petra; Steriotis, Theodore A.; et al.
Abstract : Hydrophilic oxidized carbon nanodiscs able to be used as drug delivery system and as support in nanobiocatalytic applications. Abstract : Oxidation of industrially prepared carbon nanodiscs using a simple, versatile, and reproducible approach based on the Staudenmaier method yields a new hydrophilic form of nanocarbon. As a result of the strong acid treatment, which also enables the separation of carbon nanodiscs from the mixed starting material, the graphene planes detach from the discs, while the surface of the carbon nanodiscs is decorated with various oxygen-containing functional polar groups. Thus, the completely insoluble carbon nanodiscs are converted to a hydrophilic derivative dispersable in many polar solvents, including water. The new carbon structure is expected to have a wide range of applications in several fields including bioapplications. To this end, the functionalized carbon nanodiscs exhibit very low cytotoxicity, while they achieve high drug loadings, enabling their application as an effective drug nanocarrier. Furthermore, the carbon disks were evaluated as supports in nanobiocatalytic applications, increasing significantly the stability of the systems, due to carbon disks' nano-sized dimensions.